Colors and flavors of my land: native potatoes cultivated in Boyacá - Ojeda Pérez, Zaida Zarely ; Universidad Pedagógica y Tecnológica de Colombia; Arias Moreno, Diana Marcela; Universidad Pedagógica y Tecnológica de Colombia; Bohórquez Quintero, María de los Ángeles; Universidad Pedagógica y Tecnológica de Colombia; Pacheco Díaz, José Estiben; Universidad Pedagógica y Tecnológica de Colombia; Araque Barrera, Eyda Johanna; Universidad Pedagógica y Tecnológica de Colombia (UPTC Editorial, 2021)
The potato is one of the most important foods worldwide, especially in South America where it originated. Within the potato genotypes, native potatoes are included, which are recognized for their diversity of textures, colors and flavors. This important genetic resource has been conserved and cultivated by the inhabitants of the Andean zone for many years. In Colombia, the native genotypes are cultivated and commercialized mainly in the departments of Cundinamarca, Boyacá and Nariño. However, there are some limitations that hinder its positioning at a commercial level. Among which stand out the lack of knowledge about its existence, low availability of certified seed, low rates of yield and productivity, the presence of phytopathogens due to its vegetative propagation, the lack of technology and tools to strengthen its production and the absence of focused local programs to your research and technical assistance. Therefore, a “triple helix” alliance was established between the university, private company and government in order to obtain clean traditional potato plants, characterized with ethnobotanical, agronomic, nutritional and molecular descriptors, focused on obtaining elite individuals for its agroeconomic promotion. This characterization was achieved thanks to the methodological implementation of two strategic lines, which ranged from continuous work in the laboratory and in the field through the establishment of experimental plots, to interaction with the community for the dissemination and social appropriation of knowledge. As results, effective protocols were developed to obtain clean plants of ancestral potato genotypes, using the in vitro tissue culture technique. The propagated plants were examined by microbiological techniques for the detection of fungi, bacteria and viruses. With the above, the delivery of clean native potato vitroplants to farmers in the municipalities of Ventaquemada and Chiscas in the department of Boyacá was ensured. Additionally, micropropagation ensured the molecular characterization and in vitro conservation of germplasm of native potato morphotypes of the department. In the molecular component, it was possible to establish the genetic relationships between the native potato genotypes cultivated in the department of Boyacá. This information will be the fundamental basis for the establishment of potential parental individuals in genetic improvement programs at the departmental level. In the field component, it was possible to determine the performance of each potato genotype under the conditions of two localities, finding that some of them present better development and production depending on their adaptation to the environment of the evaluated locality. It was also possible to determine the nutritional parameters of the evaluated native potato tubers. This information will allow the farmer to promote the commercialization of fresh and industrialized products, with unique organoleptic characteristics in the regional and national market. The seeding and characterization of the genotypes also creates an important milestone in the morphological identification of local genotypes. The botanical description of the flower, the arrangement of the leaves, the color of the stem, the coloration in the tuber and the plant habit are universal characters that will allow the differentiation of these plants by the community. The social appropriation of knowledge and the intervention of professionals in the different areas and disciplines, allowed the efficient use of information, giving rise to the generation of new knowledge of wide impact. Likewise, this research book shows the successful experience of linking social actors in the dissemination, generation and promotion of scientific content as a high-impact tool in favor of the promotion and encouragement of native potato genotypes. It is important to note that this book has QR codes where the reader can have direct access to the documentary entitled: “The colors and flavors of my land”, as well as three explanatory and complementary capsules to the contents of the book, integrating the scientific study, the traditional knowledge of the communities, promoting the transfer of technologies for the benefit of the producers and the territory.